MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS 5 SDN TLEKUNG 02 MELALUI MODEL MULITILITERASI - Alifia Marsha Dina; Belinda Dewi Regina; Abdurrohman Muzzaki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Language is one of the tools of knowledge. The highest competency mastered in forming language skills is reading ability. In fact, at Elementary school Tlekung 02, it was found that students reading comprehension skills were very low, as evidenced by a pre-Stage Test with only 30% of students passing. Therefore, the purpose of this study is to improve the reading comprehension skills of grade 5 students at State Elementary School Tlekung 02 Baru City by applying a multiliteracy model for reading comprehension through illustrated stories. The research method used was Classroom Action Research (CAR). The research model used was John Elliot's model conducted in 3 stages. Data collection techniques used were observation, interviews, and questionnaire distribution. The research results obtained showed an improvement in teachers' ability to enhance students' skills using the multiliteracy model. It can be seen that the scores obtained in Stage1 were 3.2, while the scores obtained in stage 2 were 3.3. For students' reading skills results, the scores obtained in stage 1 were 3.17, while the scores obtained in stage 2 were 3.85. It can be concluded that there was an increase in teacher skills and student reading skills using the multiliteracy model, with an improvement occurring over 2 stages of applying the multiliteracy model during the learning process